2018
DOI: 10.1021/acs.iecr.7b05260
|View full text |Cite
|
Sign up to set email alerts
|

Highly Adsorptive Separation of Ethane/Ethylene by An Ethane-Selective MOF MIL-142A

Abstract: In the petrochemical industry, ethane/ethylene (C2H6/C2H4) separation is one of the most important processes. Herein, we reported an iron-based metal–organic framework MIL-142A for efficiently trapping C2H6 from C2H6/C2H4 mixture, exhibiting preferential adsorption of C2H6 over C2H4. After various characterization techniques to confirm the successful preparation of MIL-142A, the C2H6 and C2H4 adsorptive separation performance was systematically investigated. Results showed that MIL-142A had remarkably higher C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 51 publications
(108 reference statements)
3
63
0
Order By: Relevance
“…The corresponding selectivity factors for MOFs reported up to now at ambient conditions are typically quite low (S < 3) with MAF-49 being the only exception with appreciable selectivity S = 9.0. [22,[28][29][30][31][32][33][34][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Theb est C 2 H 6 /C 2 H 4 absorption selectivity obtained for NIIC-20-Bu at similar conditions (S = 15.4) is 1.7 times higher than that for MAF-49 and greatly surpasses the majority of other literature results reported so far (Table S9). Other than the adsorption selectivity,the adsorption uptake is an equally important parameter for an adsorbent for gas separation applications.I nt his regard, am ore accurate evaluation of porous materials should be revealed from the selectivity vs.uptake plot.…”
Section: Forschungsartikelmentioning
confidence: 71%
“…The corresponding selectivity factors for MOFs reported up to now at ambient conditions are typically quite low (S < 3) with MAF-49 being the only exception with appreciable selectivity S = 9.0. [22,[28][29][30][31][32][33][34][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Theb est C 2 H 6 /C 2 H 4 absorption selectivity obtained for NIIC-20-Bu at similar conditions (S = 15.4) is 1.7 times higher than that for MAF-49 and greatly surpasses the majority of other literature results reported so far (Table S9). Other than the adsorption selectivity,the adsorption uptake is an equally important parameter for an adsorbent for gas separation applications.I nt his regard, am ore accurate evaluation of porous materials should be revealed from the selectivity vs.uptake plot.…”
Section: Forschungsartikelmentioning
confidence: 71%
“…Multicomponent column breakthrough experiments mimicking industrial mixtures comprising ethane, ethylene, methane, and carbon dioxide confirmed that ethane was retained in the column for the longest time and polymergrade ethylene (purity >99.95%) could be obtained with relatively high efficiency. Other ethane-selective MOFs include PCN-250, [66] PCN-245, [65] ZIF-7, [71][72] MIL-142, [64] and recently reported Cu(Qc) 2 [67] and MUF-15. [61]…”
Section: Background and Representative Examples Of Thermodynamic Sepamentioning
confidence: 99%
“…The mass loss of 32.1% for H 4 bptc is close to the theoretical value (32.4%) calculated from the formula Zr 6 O 4 (OH) 4 (bptc) 3 . Therefore, Zr‐bptc is thermally stable to 702 K. The thermal decomposition temperature of Zr‐bptc (702 K) outperformed most reported ethane‐selective MOFs, such as IRMOF‐8 (673 K), PCN‐250 (673 K), PCN‐245 (625 K), Ni(bdc)(ted) 0.5 (673 K), ZIF‐69 (643 K), and MIL‐142A (573 K), but slight lower than UiO‐66 (739 K) . The high thermal stability of Zr‐bptc and UiO‐66 probably lies on the strong Zr‐O coordination bonds and the 12‐connected Zr 6 (μ 3 ‐O) 4 (μ 3 ‐OH) 4 (COO) 12 SBU of Zr‐bptc and UiO‐66.…”
Section: Resultsmentioning
confidence: 94%
“…The adsorption selectivities decrease sharply from 5.5 (ethane/ethylene = 1:1) and 6.6 (ethane/ethylene = 1:15) to 1.4 (ethane/ethylene = 1:1 or 1:15) at <1 kPa region, and the selectivity nearly keeps the constant of 1.4 at 1–100 kPa. The adsorption selectivity of Zr‐bptc (1.4) at 298 K and 100 kPa is moderate (Table S3), and the selectivity is comparable to activated carbon (1.2), C‐PDA‐5 (1.51), ZIF‐4 (1.5), MIL‐142A (1.5), and Cu(ina) 2 (1.25) . But the ethane/ethylene selectivity of Zr‐bptc is slightly lower than PCN‐245 (1.80) and Ni(bdc)(ted) 0.5 (1.85) .…”
Section: Resultsmentioning
confidence: 97%